Perlindungan Hukum Bagi Investor Dalam Pasar Modal - Hilda Hilmiah Dimyati (Jurnal Cita Hukum, 2014)
Abstract: Legal Protection for Investors in the Capital Market. Supervision in the financial services industry capital markets experienced a change of control by Bapepam-LK be supervised by the Financial Services Authority. Institutionally, Bapepam-LK is responsible to the Minister of Finance, as Bapepam-LK is under the auspices of the Ministry of Finance, while the Financial Services Authority is responsible to Parliament or the public. Crucial aspect on which the formation of the FSA is not maximum protection of the interests of consumers of financial services. In accordance with the problems that occur as above, the authors feel the need to examine the legal protection in the capital market. This writing will also examine the parties are entitled to legal protection based on Law No. 8 of 1995 and the Capital Market Law No. 21 of 2011 on the Financial Services Authority. Abstrak: Perlindungan Hukum Bagi Investor Dalam Pasar Modal. Pengawasan di bidang industri jasa keuangan pasar modal mengalami perubahan dari pengawasan yang dilakukan oleh Bapepam-LK menjadi diawasi oleh Otoritas Jasa Keuangan. Secara kelembagaan, Bapepam-LK bertanggung jawab kepada Menteri Keuangan, karena Bapepam-LK berada di bawah naungan Kementrian Keuangan, sedangkan Otoritas Jasa Keuangan bertanggung jawab kepada Dewan Perwakilan Rakyat atau masyarakat. Aspek krusial yang menjadi dasar pembentukan OJK adalah tidak maksimalnya perlindungan kepentingan konsumen jasa keuangan. Sesuai dengan permasalahan yang terjadi seperti diatas, maka penulis merasa perlu untuk meneliti tentang perlindungan hukum di pasar modal. Penulisan ini juga akan meneliti para pihak yang berhak atas perlindungan hukum berdasarkan pada Undang-Undang Nomor 8 Tahun 1995 Tentang Pasar Modal dan Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan. DOI: 10.15408/jch.v1i2.1473